Social Support and its Association with Sociodemographic Characteristics, Dietary Patterns, and Perceived Academic Stress among College Students in Puerto Rico - Pagán, Ideliz; Fabián, Carla; Ríos, Josué L.; Betancourt, Jesmarie; Cruz, Sonia Y.; González, Anaisa M.; Rivera-Soto, Winna T. (Puerto Rico Health Sciences Journal, 2013)
Objective: The objective of the present study was to determine the association between social support, dietary pattern, and academic stress among college students in Puerto Rico, based on their socio-demographic characteristics. Methods: This was a retrospective, descriptive, epidemiological study that used a stratified sample of 275 college students. The data collection was done by means of a self-administered instrument. Results: Most of the participating students were female (67.6%), ranged in age from 21 to 30 years (88%), and had health weights (56.4%); a large minority, 42.7%, lived in homes having low annual incomes. Most of the participating students perceived their academic loads as being heavy (68.2%) and their total academic stress levels as being moderate (60.7%). Most of the students had moderate levels of social support (61.5%). Social support was significantly associated with age (p = 0.04), in that young students had high levels of social support; with the school being attended (p = 0.01), in that students from the School of Dental Medicine had high levels of social support’ and with perceived academic load (p = 0.02). Social support was significantly associated with age (p = 0.04), in that the younger students had higher levels of social support than did their older counterparts; with the school being attended (p = 0.01), in that students from the School of Medicine had higher levels of social support than did the students from the other schools; and with perceived academic load (p = 0.02). Conclusion: There were associations between social support and age, school, and perceived academic load, but there were no such associations between social support and either level of academic stress or dietary pattern.